Literacy in the Global Village. - Carroll, Margaret (International Journal of the Book, 2007)
Advancements in communication, literacy, and technology have historically been dependent on and influenced by each other. Forms of participatory government have been contingent upon these developments as well. The Gutenbergera printing press essentially ushered in an era of mass communication and encouraged literacy. The printing press also made democratic forms of government possible. The marketplace of ideas made possible by mass communication is a basic tenet on which the United States' Constitution's First Amendment protection of a free press is grounded. The Internet has been compared to the Gutenberg-era press as a new technology that may serve to extend democracy because it expands the marketplace of ideas even further than the printing press did, not only making possible the wide dissemination of opinions and ideas, but also eliminating one hindrance to free exchange of ideas—the gatekeeper. The question is whether new media, specifically the Internet, will serve to expand democracy or whether the opposite effect will occur. If the Internet is to influence the expansion of democracy and literacy in the same ways the printing press did, access to the technology for all groups in society and media literacy education must empower individuals to participate in public affairs. The existence of the new media technology makes media literacy necessary just as the printing press made traditional literacy necessary. The challenge then is to extend the promise of progress brought about by the newest forms of communication technology to all segments of society, much in the same way campaigns for universal literacy attempted to increase the knowledge and power of individuals in the past.